Weed community composition in different agro-systems - Cardoso, Isabella Sichierski; Jakelaitis, Adriano; Soares, Michellia Pereira; Araújo, Vinícius Tavares de; Cabral, Paulo Henrique Ramos (Comunicata Scientiae, 2017)
Weed communities in agricultural systems are diverse and subjected to different agronomic practices. In this study, a phytosociological survey of the weed community in different cropping systems consisting of corn, horticulture, perennial cultivation of Jatropha curcas and pasture of Urochloa brizantha in Rio Verde, GO, Brazil, was carried out. Assessments were performed at the beginning (October 2011) and at the end (March 2012) of the rainy season. After identifying and counting species, were calculated the phytosociological indices of density, frequency, abundance and relative importance, as well as the diversity index of Shannon-Wiener, evenness index of Pielou and similarity coefficient of Sorense. Were found 46 species of sixteen families, especially Poaceae. The most important species were: Alternanthera tenella in the annual growth environment during the both periods; Panicum maximum (early rainy season) and Chamaescy hirta (end of the rainy season) in the vegetable garden; Eleusine indica (early rainy season) and Galinsoga parviflora (end of the rainy season) in the perennial crop and Sida rhombifolia (early rainy season) and Neonotonia wigrtii (end of the rainy season) in the pasture. Lower diversity indices and evenness were observed in the pasture environment. Sampling time presented a higher impact on similarities when compared to the different environments.